Variabel – variabel dan efeknya dalam kalkulasi tingkat keausan ban yang didasarkan atas model matematis - Eduardo Wangsa Saputra; Henky Suskito Nugroho (Jurnal Teknik Mesin Indonesia, 2022)
Even though tires are the only contact points of a vehicle with the road below, the tires received less attention in the development of vehicle monitoring technology. Determining the pressure of the tires is important, but about 67% of drivers cannot determine their tires conditions and do not know when to replace their worn-out tires. The tire wear is important as it increases the probability of hydroplanning. This study is created in order to provide a new insight of the effect of different driving behaviours to the wear of the tire. In order to know what variables causes greater wear to a tire, a simulation that represents the real-life conditions are required. The simulations will be made by using formulas based on Brush model and Savkoor model. Weight shift model is also implemented in order to obtain a more realistic number. Each condition is isolated with others to gain a clearer difference between conditions. From the simulations one, it is found that the greater the driving angle, the greater the tire wear. The greater the acceleration also provide a difference in the tire wear due to the weight of one side of a vehicle is heavier while the other is lighter. The greater the load or weight the tire sustain, the greater that tire’s wear. On the other hand, tire pressure pose little difference compared to the other variables.